2000
DOI: 10.1152/ajpregu.2000.279.5.r1531
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen limitation of thermal tolerance defined by cardiac and ventilatory performance in spider crab,Maja squinado

Abstract: Frederich, Markus, and Hans O. Pö rtner. Oxygen limitation of thermal tolerance defined by cardiac and ventilatory performance in spider crab, Maja squinado. Am J Physiol Regulatory Integrative Comp Physiol 279: R1531-R1538, 2000.-Geographic distribution limits of ectothermal animals appear to be correlated with thermal tolerance thresholds previously identified from the onset of anaerobic metabolism. Transition to these critical temperatures was investigated in the spider crab (Maja squinado) with the goal of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
273
3
5

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 318 publications
(304 citation statements)
references
References 40 publications
18
273
3
5
Order By: Relevance
“…In this context, the question has regained interest whether limitations in oxygen availability or supply are involved in thermal limitation. Early evidence collected in marine invertebrates (annelids and sipunculids) demonstrated a transition to anaerobic metabolism (including mitochondrial anaerobiosis) at both cold and warm temperature extremes (Zielinski and Pörtner, 1996;Sommer et al, 1997), later on confirmed in crustaceans (Frederich and Pörtner, 2000) and molluscs, i.e. bivalves, gastropods and cephalopods (Pörtner and Zielinski, 1998;Pörtner et al, 1999;Peck et al, 2002;Sokolova and Pörtner, 2003).…”
Section: Introduction: a Role For Hypoxia In Thermal Limitation?mentioning
confidence: 97%
See 3 more Smart Citations
“…In this context, the question has regained interest whether limitations in oxygen availability or supply are involved in thermal limitation. Early evidence collected in marine invertebrates (annelids and sipunculids) demonstrated a transition to anaerobic metabolism (including mitochondrial anaerobiosis) at both cold and warm temperature extremes (Zielinski and Pörtner, 1996;Sommer et al, 1997), later on confirmed in crustaceans (Frederich and Pörtner, 2000) and molluscs, i.e. bivalves, gastropods and cephalopods (Pörtner and Zielinski, 1998;Pörtner et al, 1999;Peck et al, 2002;Sokolova and Pörtner, 2003).…”
Section: Introduction: a Role For Hypoxia In Thermal Limitation?mentioning
confidence: 97%
“…A temperature dependent optimization of oxygen supply capacity was visible in the form of maximized arterial P O 2 within a limited temperature range, equivalent to the window of mean temperatures in the natural environment (Frederich and Pörtner, 2000). Limitation of both ventilatory and circulatory capacities towards thermal extremes was found to explain these patterns of body fluid oxygenation (Zielinski and Pörtner, 1996;Frederich and Pörtner, 2000).…”
Section: Introduction: a Role For Hypoxia In Thermal Limitation?mentioning
confidence: 97%
See 2 more Smart Citations
“…hypoxia) only if the conductance of oxygen flow increases and there is indeed a number of mechanisms to fulfil this precondition (increasing ventilation, increasing blood circulation, etc. ; Frederich and Po¨rtner 2000). However, all of these mechanisms have certain limits of functional capacity.…”
Section: Critical Oxygen Concentrationmentioning
confidence: 99%